Conductivity inversion of methyl viologen-modified random networks of single-walled carbon nanotubes. (15th January 2023) - Przewłoka, Aleksanda; Rehman, Adil; Smirnov, Serguei; Karpierz-Marczewska, Ewelina; Krajewska, Aleksandra; Liszewska, Malwina; Dróżdż, Piotr; Pavłov, Krystian; Dub, Maksym; Novytskyi, Serhi; Jankiewicz, Bartłomiej; Mierczyk, Zygmunt; et al.
Abstract: One of the challenges of using carbon nanotubes electronics is achieving precise control of the conductivity type. It is particularly difficult to obtain the n-type conductive nanotubes. One of the most common methods of CNTs modification allowing to change their conductivity type is chemical functionalization. This paper describes the results of studies on non-covalent modification of randomly oriented single-walled carbon nanotubes (SWCNT) layers with methyl viologen (MV), which allows for the change of the conductivity of SWCNT from p - to n -type. The properties of pristine and MV-modified SWCNT have been compared using Scanning Electron Microscopy, Raman spectroscopy, and X-ray Photoelectron Spectroscopy. The SWCNT conductivity type change was confirmed by photo-conductance under ultraviolet illumination and measurements in the field effect transistor configuration. Graphical abstract: